SPINKs in Tumors: Potential Therapeutic Targets - Liao, Chengcheng; Wang, Qian; An, Jiaxing; Zhang, Minglin; Chen, Jie; Li, Xiaolan; Xiao, Linlin; Wang, Jiajia; Long, Qian; Liu, Jianguo; Guan, Xiaoyan (Frontiers in Oncology, 2022)
The serine protease inhibitor, Kazal type (SPINK) family includes SPINK1-13 and is the largest branch in the serine protease inhibitor family. SPINKs play an important role in pancreatic physiology and disease, sperm maturation and capacitation, Nager syndrome, inflammation and the skin barrier. Evidence shows that the unregulated expression of SPINK1, 2, 4, 5, 6, 7, and 13 is closely related to human tumors. Different SPINKs exhibit various regulatory modes in different tumors and can be used as tumor prognostic markers. This article reviews the role of SPINK1, 2, 4, 5, 6, 7, and 13 in different human cancer processes and helps to identify new cancer treatment targets.